Perencanaan Penggunaan Lahan Berbasis Kemampuan Lahan di Kelurahan Kulaba, Kecamatan Ternate Barat, Kota Ternate - Robo, Sarif; Ladjinga, Erwin; Hartono, Gunawan; Sofyan, Adnan; Mustaan, Sukmawati (Jurnal Pertanian Khairun, 2023)
Land use planning is the process of inventorying and assessing the status, potential and limitations of a given area and its resources, which local people interact with or with people who care about the area to determine their needs, wants and aspirations. for the time. Kulaba sub-district is a small part of Ternate City which is located in West Ternate sub-district, which has a characteristic sloping to steep topographic area. The purpose of this study is to plan land use based on land capability, which is in the Kulaba Village, so that it becomes information in farming and other businesses. Determination of sampling points using a map then carried out a land survey with a free survey observation distance system, the approach used is analytic. Classification of land capability is categorized based on the characteristics that are potential and obstacles in its use. This analysis uses the LCLP (Land Classification and Landuse Planning) application. The results showed land use planning based on land capability that the land at the research location in Kulaba Village had four land capability classes namely III, IV, VI and VIII with the limiting factor of surface slope (L), soil permeability (P) and erosion sensitivity (KE). and subsoil texture with an area of 259.4 Ha. The alternative is that C-organic must have an important role in determining the soil's ability to support plants.